Macrophytes, ecosystem services and potentialities of ecotourism in some lakes of eastern Nepal - Siwakoti, Eliza Acharya; Baniya, Chitra Bahadur; Mandal, Tej Narayan (Our Nature, 2025)
Lakes in the eastern Nepal enriched with a combination of mystical biodiversity and the essence of cultural ecosystem services are among the major ecotourism destinations. Wetland based ecotourism approach aims at conserving the environment and uplifting the socio-economic and cultural conditions through tourism development. The study aimed to list out the macrophytes of the lakes and to assess the ecotourism potentialities in some lakes (Taltalaiya, Raja-Rani, Chulachuli and Maipokhari) of eastern Nepal. Macrophytes were studied by quadrat method. Regarding the data for the components of ecotourism, primary data were collected by key informant survey and focus group discussion to know the visitor’s perception on the current ecotourism status of these lakes. Secondary sources of data collection included published and unpublished literature. Collected data were analyzed both qualitatively and quantitatively. The rich macrophyte diversity of these lakes comprising 56 species of angiosperms and 4 species of aquatic pteridophytes reflects a natural and undisturbed habitat with great ecotourism potentials. However, Chulachuli lake is not familiar from ecotourism point of view till date. Based on numerous ecotourism activities, the study reveals that relaxation ranks top in Taltalaiya lake, picnic/outing in Raja-Rani lake, and religious activity in Maipokhari lake. Ecotourism activities integrated with public involvement could serve as a backbone for generating and improving the wetland revenue to sustain the conservation of wetland biodiversity.